2011
DOI: 10.1039/c0dt00923g
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of four new CoII/CoIII and NiII complexes with a pentadentate Schiff base ligand: syntheses, structural descriptions and magnetic studies

Abstract: In this paper we report the temperature and pH dependent syntheses and systematic characterization of four new Co(II)/Co(III) and Ni(II) complexes with a pentadentate Schiff base ligand H(3)L obtained by condensing 1,3,-diaminopropan-2-ol with 2-hydroxyacetophenone in 1:2 molar ratio. The room temperature syntheses involving Co(II) and Ni(II) nitrates and the ligand H(3)L lead to the isolation of the dinuclear species [Co(2)L(2)(H(2)O)] (1), and the mononuclear complex [Ni(LH)] (3), respectively, whereas reflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…This slight decrease in χ M T observed at lower temperatures could be due to zero field splitting (ZFS) . The M vs. H plots at 5–10 K show that rate of increase of magnetization is slow.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This slight decrease in χ M T observed at lower temperatures could be due to zero field splitting (ZFS) . The M vs. H plots at 5–10 K show that rate of increase of magnetization is slow.…”
Section: Resultsmentioning
confidence: 97%
“…It has been observed that ferromagnetic magnetic exchange interaction is observed when M–O–M bond angle is lower than 98° . In the complex 4 bond angles of Ni(1)–O(2)–Ni(2) and Ni(2)–O(4)–Ni(1) are 96.97 and 95.38 0 which fall well below 98 0; therefore, Ni II ions in the complex 4 exhibit ferromagnetic exchange interactions , . At 15 K, sharp increase in χ M T value indicates very strong ferromagnetic interaction and complex exhibits super‐magnetic behavior at this temperature.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Co 2+ ions are in a compressed distorted octahedral environment with slightly distorted O h symmetry, in such case the ground orbital triplet 4 T 1g splits into two states 4 A 2g and 2 E g by distortion on the octahedral geometry; these were also split into six sub‐states by spin‐orbit interactions . In order to avoid over parameterization while calculating magnetic data, conventional approximate axial distortion was considered in each case.…”
Section: Resultsmentioning
confidence: 99%
“…Schiff bases are also used as significant intermediates for synthesis of various bioactive materials [6][7][8][9]. Countless Schiff bases and their coordination complexes with outstaning antimicrobial activity, antifungal, and anticancer abilities have been reported [8][9][10][11][12][13]. The Schiff bases with pyridine ring have received more attention in literature [14][15].…”
Section: Introductionmentioning
confidence: 99%